Knowledge, attitude, and practice among Bangladeshi adults with hypothyroidism (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Treatment success depends on the knowledge, attitude, and practice (KAP) of patients with hypothyroidism. Comprehensive data on KAP regarding hypothyroidism was not adequately evaluated among Bangladeshi people.Objectives: To evaluate KAP among Bangladeshi adults with hypothyroidism.Methods: This cross-sectional questionnaire based KAP survey was done between June 2022 and March 2023 among 527 eligible adults [Age (years): 35.1±10.5, mean±SD; m/f: 14.6%/85.4%]. Baseline characteristics and responses to 27 questions and statements of KAP were collected from participants in government hospitals and doctors' private chambers from six districts. A specific mark was given for each response. The average marks obtained by each participant were categorized into three tertiles for each domain. The baseline characteristics were compared across the tertiles.Results: Nearly 34.5% of the participants correctly answered the 14 questions of the knowledge domain. About 78.9% agreed with all five statements of the attitude domain. Almost 45.7% regularly followed all eight good practices in their disease management. Those with negative attitudes had a lower frequency of individuals under 30 years (adjusted standardized residual, ASR = -3.2) and a higher frequency of those over 50 years (ASR = +3.4). For those with education below the secondary level, the frequency of negative attitudes (ASR = +6.0) was higher, while the frequency of positive attitudes (ASR = -4.1) was lower. The frequency of older people (>50 years, ASR = -3.4) and those with lower education (below secondary, ASR = -4.3) was lower, but the disease duration was shorter (